Experimental assessment of 10 Gbit/s SSB OFDM IM-DD systems performance employing raised-cosine based symbol precoding - Cruz, P. E. D.; Alves, T. M. F.; Cartaxo, A. (Journal of Lightwave Technology, 2014)
The performance improvement of 10 Gbit/s single-sideband orthogonal frequency division multiplexing intensity-modulated direct-detection systems achieved by reducing the signal peak-to-average power ratio (PAPR) with a symbol precoding technique based on the raised-cosine pulse, without and with bandwidth expansion, is evaluated experimentally. The impact of pre-emphasis (PE), necessary to mitigate the setup frequency limitations, on the PAPR reduction achieved by symbol precoding is investigated. At the input of the optical modulator, PAPR reductions of ~ 3 dB with PE and without PE are achieved using the precoding technique without band excess; with precoding with band excess of 25%, PAPR reductions of ~ 4 dB with PE and 4.5 dB without PE are obtained. Due to precoding, a bit error ratio (BER) improvement of almost two orders of magnitude is shown along 150 km standard single mode fiber transmission, for BERs around 10 -4 . In addition, it is also shown that precoding enables similar BER improvement with 75 km fiber propagation when nonlinear fiber effects are moderate.